Cost- and Price Dynamics of Solar PV Modules - Stefan J. Reichelstein; Anshuman Sahoo (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper develops a model framework and a corresponding empirical inference procedure for estimating long-run marginal cost in industries where production costs decline over time. In the context of the solar photovoltaic module industry, we rely on firm-level financial accounting data to estimate the long-run marginal cost of PV modules for the years 2008 -2013. During those years, the industry experienced both sharp price declines and significant expansions of manufacturing capacity. By comparing the trajectory of average sales prices with the long-run marginal cost estimates, we are in a position to quantify the extent to which actual price declines were attributable to excess capacity as opposed to reductions in production costs. While we find a significant effect attributable to excess capacity for some quarters in our sample period, the dynamics of this industry also points to a rate of cost reductions that is even faster than the 80% learning curve which has described the trajectory of average sales prices over the past three decades.
Keywords: D41; L11; L63; M21; Q42; 330; long-run marginal cost; cost estimation; learning-by-doing; price dynamics